Design and acceptance test of compact planar monopole antenna for LTE smartphone considering SAR, TRP, and HAC values. (19th August 2019) - Das, Saumya; Bose, Tanushree; Islam, Hashinur
Summary: Eight different types of compact multiband planar antennas are proposed in this work for covering several long‐term evaluation (LTE) and Wi‐Fi bands in a smartphone antenna design. Gradual inclusion of several sections of a radiator on an inexpensive FR4 substrate is presented for receiving multi‐LTE bands with a handset device. Along with the presently available LTE bands, this antenna design approach also includes upcoming LTE in unlicensed spectrum and LTE licensed‐assisted access. Various techniques such as partial ground, branch line slit, parasitic structure, and meandered lines are used to achieve desired resonant frequencies, bandwidth, matching, and miniaturization. The final type of eight antennas has been implemented in the real‐world mobile phone handset. The interaction between the mobile handset and the human phantom model has been analyzed at few specific frequencies for evaluating specific absorption rate (SAR) and total radiated power (TRP) in a simulated manner. The same type is also studied as a hearing aid compatibility (HAC)–supported wireless device. The simulated results show the SAR and HAC values are at the acceptance level for this proposed design. A prototype model is developed and few parameters are measured for validation. Abstract : The key findings include the following: Design of eight different types of compact mobile handset antennas for LTE bands. Specific absorption rate measurements on human head for proposed final antenna type. Hearing aid compatibility measurements in the near field region for the proposed final antenna type.